2018
DOI: 10.15761/tim.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Patho-physiological studies of human blood with kidney dysfunction and therapeutics of albumin functionalized silver nanoparticles in mice kidney cells in vitro

Abstract: The incidence of acute kidney injury and disease is increasing alarmingly. Inflammatory or nutritional status are associated with kidney disease/ Serum albumin is the marker to identify malnutrition in patients with chronic kidney disease. Treatment with albumin functionalized green synthesized silver nanoparticles help maintain and restore normal cellular function in the kidney. The role of albumin in kidney cell metabolism was studied in-vitro and showed a profound influence of albumin with or without nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The accumulating silver ions and particles accelerated renal cell toxicity and destruction (Tiwari et al, 2017). Renal function may also be impacted by changes in albumin concentration as albumin aids in the transportation of medications that lower oncotic pressure, hormones, metals, and vitamins (Sironmani & Bhattarai, 2018). This was evaluated in the current study based on the serum levels of creatinine, urea, and uric acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulating silver ions and particles accelerated renal cell toxicity and destruction (Tiwari et al, 2017). Renal function may also be impacted by changes in albumin concentration as albumin aids in the transportation of medications that lower oncotic pressure, hormones, metals, and vitamins (Sironmani & Bhattarai, 2018). This was evaluated in the current study based on the serum levels of creatinine, urea, and uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination of the kidney in the present work showed extensive necrosis in the renal tubules in both the cortex and medulla. Marked alteration in the renal tubular cells could be the reason for heightened glucose levels in this group as glucose is reabsorbed by proximal tubular cells (Sironmani & Bhattarai, 2018). Concerning the histopathological alterations in the liver of the fetuses, the present study reported notable alterations in the hepatic parenchyma in agreeing with Elsharawy et al (2020), such as vacuolization, degeneration, and necrosis of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%